Religious and spiritual beliefs and practices in medicine: an evaluation in a tertiary care hospital in Malaysia - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Akter, Seikh Farid Uddin; SMS, Azarisman; Omar, Ahmad Marzuki (Ibrahim Medical College, 2010)
In recent years there has been growing awareness regarding the role of religion and spirituality (R/S) in the practice of clinical medicine. Despite hundreds of articles in professional journals on the subject, little is known about physician beliefs regarding the influence of religion on health. We aim to assess the beliefs and observations of physicians regarding the role of R/S and patient’s health and whether they address such issues in their clinical practice. Concomitantly, we aim to assess the beliefs of our patients and whether they like to address such issues. Questionnaire was based on a cross sectional survey among hospitalized patients and their treating physicians. Nearly all patients and physicians reported a high prevalence of religiosity. Patients also acknowledged that their R/S was respected by the staff, and that physicians inquired R/S about half of the time. R/S was described as beneficial as it enabled patients to cope better with their illness and gave them a positive state of mind. Religion is important to many patients and physicians, but half of the physicians ignore it in their clinical practice. Physicians need to be attentive to patients R/S issues and address them in specific clinical situations.